An Analysis of The Roles of Key Players In The Governance of Civil Service Neutrality During The 2020 South Sumatra Regional Elections - Shelly Aulia Ramadhanti; Andy Alfatih; Katriza Imania (LP2M IAIN Palopo, 2026)
This research focuses on the extent to which the neutrality of the Aparatur Sipil Negara (ASN) is achieved through the implementation of the Pemilihan Kepala Daerah 2020 (Pilkada) which were held simultaneously in almost all regions of Indonesia. This is considering that the neutrality of ASN can be said to be one of the keys to success in holding honest and fair general elections. In conducting a further review of the implantation of ASN Neutrality in the 2020. Pilkada which is analyzed based on the theory put forward by Sarah and Steve (1997). The method used in this research is descriptive qualitative with an inductive approach. Data collection techniques, documentation, and observation with 4 research informants, namely from Bawaslu Provinsi Sumatera Selatan and Komisi Aparatur Sipil Negara. In conclusion, the ACTORS analysis in responding to reports of violations of ASN neutrality is reviewed from the theory put forward by Sarah Cook and Steve (1997) based on the dimensions of Authority, Confidence and Competence, Trust, Opportunities, Responsibilities, and Support have an impact on the success of following up ASN neutrality in South Sumatera. The advice that the author can give is that those who have the authority to determine the appointment, transfer and dismissal of ASN are no longer political officials, that is but the highest career officials in the region.